Understanding to Concept of Jarajanya Vyadhi (ageing related diseases) w.s.r. to Sandhigatavata (osteo arthritis) (International Journal of Ayurveda and Pharma Research, 2024)
As age advances Vata Dosha increases in an individual. This increasing Vata trigger and accelerates Dhatu Kshaya (depletion of tissues) and Bala Kshaya (diminished the body strength). Hence advancing age makes man prone to many diseases especially degenerative disorders. Asthis (bones) are the main seat of Vata Dosha and Sandhis (joints) is the main seat of Kapha Dosha. Vata Dosha is responsible for different body movements like Prasaarana and Akunchana of Sandhi (flexion and extension of joints), whereas Shleshaka Kapha located in Sandhi (joints) is provides nutrition, protection and to minimize the friction during the movement. Sandhigatavata is Vata pradhana vyadhi. It is quite similar to osteoarthritis, a degenerative joint disease stand in modern medical science. Sandhigatavata is Vata dominating disorder which result in inflammatory and degenerative changes in joints. Osteoarthritis is a disease of musculoskeletal system, affecting the joints mostly in elderly population and in weight bearing joints (particularly knee joint). The current standard modern medical pharmacological management of osteoarthritis includes the administration of analgesics and non-steroidal anti-inflammatory drugs (NSAIDs).  However, their use neither provides adequate and significant relief in symptoms nor deceleration in disease process. Therefore, Vata shamaka aushadhis along with local application e.g. Abhyanga, different form of Swedana are beneficial. As Sandhigatavata is ageing related heath condition, Rasayana chikitsa can also be helpful in the management of Sandhigatavata (Osteoarthritis). This article enlighten the knowledge about Jarajanya vyadhi especially Sandhigatavata.